A simple approach for education using virtual human dataset - Seng, W.C.; Mirisaee, S.H. (2011)
The virtual tour of human body is a system which is able to generate a three â dimensional image of a human bodybased on the human dataset. Virtual human body systems prepare an environment for medical practitioners to treat certainmedical conditions especially those which require surgery, precision and planning according to individual patients. Currentvirtual human body systems have some drawbacks and shortages especially as a study aid system, so the proposed system inthis research tries to fulfill the shortages as a proper study aid system. The objective of this research is to develop a systemthat can simulate fly â through of a specific human organ which enables 3D views of the human body in the form of ComputedTomography (CT) scan, Magnetic resonance Imaging (MRI) scan as well as the actual anatomical images. The proposedsystem also provides cross section view of a particular organ or the whole body which are sectioned either horizontally orvertically and allows selection of organ view or cross section view. Two different methods have been implemented in thisresearch, namely surface rendering and volume rendering to achieve better quality for 3D images. As a conclusion,advantages of proposed system like manipulating the organs, simplicity and low cost makes it suitable to use by medicalstudents for in-depth study of the human anatomy or being used by biology teachers in high schools as part of the teachingguide.